2019
DOI: 10.1177/0269881119864968
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of agomelatine for the treatment of sleep problems in adults with autism spectrum disorder and co-morbid intellectual disability

Abstract: Purpose: Intellectual disability (ID) and autism spectrum disorder (ASD) are common, co-occurring developmental disorders and are frequently associated with sleep problems. This study aimed to assess the effectiveness and tolerability of agomelatine as a pharmacotherapy for sleep problems in ASD adults with ID. Method: A randomised, crossover, triple-blind, placebo-controlled clinical trial, with two three-month periods of treatment starting with either agomelatine or placebo and a washout period of two weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…The findings of the included studies are summarised in Table 1. 2034 Two RCTs on old-generation antidepressant tricyclics were on clomipramine, both of which were small crossover trials ( n = 24 and 36); 24,25 one compared clomipramine with desipramine and placebo, 24 and the other with haloperidol and placebo. 25 One found clomipramine to be marginally significantly better than placebo in treating ASD core symptoms like RRB, 24 but the other one did not show any significant inter-group difference.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The findings of the included studies are summarised in Table 1. 2034 Two RCTs on old-generation antidepressant tricyclics were on clomipramine, both of which were small crossover trials ( n = 24 and 36); 24,25 one compared clomipramine with desipramine and placebo, 24 and the other with haloperidol and placebo. 25 One found clomipramine to be marginally significantly better than placebo in treating ASD core symptoms like RRB, 24 but the other one did not show any significant inter-group difference.…”
Section: Resultsmentioning
confidence: 99%
“…A crossover trial of 23 adults showed improvement in night total sleep time but no other sleep parameters during agomelatine treatment, but not in the placebo phase. 20 No ASD core symptoms were assessed in this study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations